Understanding Snow Microstructure for Microwave Remote Sensing. Issue 47 (25th November 2014) - Sandells, Mel; Hörhold, Maria; Rutter, Nick
<x xml:space="preserve">Abstract</x> Scientists from the snow and soil remote sensing communities met to build on recent developments in objective snow microstructure measurement techniques by improving the understanding of their application in remote sensing at microwave frequencies.